Clinically significant, nontraumatic, degenerative joint disease of the temporomandibular joints in a horse. (13th June 2015) - Smyth, T.; Allen, A. L.; Carmalt, J. L.
Summary: Horses with degenerative joint disease (DJD) of the temporomandibular joint (TMJ) have been reported infrequently, with the majority of cases describing the disease as a consequence of an earlier traumatic event. A case of clinically significant TMJ‐DJD due to a nontraumatic event has not been published. This retrospective case report describes a case of bilateral, DJD of the TMJ. Case management, subsequent review and interpretation of the clinical records, tangential radiographic views of each TMJ, computed tomography and magnetic resonance imaging of the head, and post mortem histological examination of the TMJs were performed. The horse exhibited both quidding and a 'clicking' sound during mastication; episodes of intermittent colic were also prevalent in the horse's history. Computed tomography illustrated bilateral mineralisation of the rostral aspect of both intra‐articular discs. Treatment, by intra‐articular injection of corticosteroid, resulted in temporary resolution of both the quidding and the 'clicking' sound, as well as the recurrent episodes of colic. Repeated treatment over time was required. Ultimately the horse was subjected to euthanasia for reasons other than disease of the TMJ. The development of TMJ‐DJD may not be confined to traumatic events. Age‐related degeneration of this joint may occur and manifest through quidding and abnormal sounds noted during mastication.